Papel da cetamina sobre receptores TRPV1 da via sensorial aferente periférica: implicações celulares e moleculares - Flavia Lage Pessoa da Costa (2017)
Ketamine is an intravenous anesthetic used for induction of anesthesia, as an adjuvant to local anesthesia, for sedation of patients in intensive care, to induce analgesia in burned patients and in dental and veterinary procedures. Ketamines mechanism of action involves interaction with multiple sites including glutamatergic NMDA and non-NMDA receptors, muscarinic and nicotinic cholinergic receptors, opioid and monoaminergic receptors. Sub- anesthetic doses are used in postoperative pain therapy and chronic pain. The TRPV1 is a nonselective cation channel which is expressed in nociceptive fibers. It is present in capsaicin-sensitive neurons and approximately 50% of dorsal root ganglia (DRG). In this study we investigated ketamines effect on TRPV1 receptors present in peripheral sensory pathway. HEK-293 cells transfected with TRPV1 receptors were stimulated or incubated with different anesthetic concentrations and evaluated for changes in [Ca2+]i using a fluorometer machine. The results have suggested that although ketamine didnt activate the receptor directly it potentiates the capsaicin response in transfected cells. DRG cultures were performed and analyzed in confocal microscopy. The experiments confirmed the previous results and suggests that ketamine could prevent DRGs desensitization induce by capsaicin successive stimulations via activation of PKC. Western blotting experiments indicated that phosphorylated TRPV1 and phosphorylated PKC protein expression levels were increased in anesthetics presence. DRGs culture pretreatment with ketamine reduced the amount of capsaicins responsive neurons regardless the neurons size. MTT cell viability experiments were performed and suggest that ketamines incubation has a cytotoxic effect on DRGs cultures that promotes reduction in 20% in the amount of nociceptive fibers responsive to capsaicin. Behavioral experiments corroborate results found in vitro. Taken together our data indicate that ketamine modulates TRPV1 sensitivity to capsaicin through a mechanism dependent of receptor phosphorylation by PKC.